Revision Total Knee Arthroplasty With the Use of Restricted Kinematic Alignment Protocol: Surgical Technique and Initial Results - Kostretzis, Lazaros; Roby, Gabriel Bouchard; Martinov, Sagi; Kiss, Marc-Olivier; Barry, Janie; Vendittoli, Pascal-André (Frontiers in Surgery, 2021)
Background and Objectives: Kinematic alignment (KA) for primary total knee arthroplasty (TKA) has been shown to provide equivalent or better results to mechanical alignment (MA). The use of KA in the setting of revision TKA, aimed at restoring the individual knee anatomy, kinematics, and soft-tissue balance, has not been documented yet. The purpose of this study is to describe the technique for performing TKA revision using the restricted KA (rKA) protocol and to report (1) rerevision rate and adverse events, (2) patient reported outcome measures (PROMs), and (3) radiological signs of implant dysfunction related to this technique. Methods: The rKA protocol was used in 43 selected TKA revisions cases suitable for the technique. Adverse events, reoperation, revision, and their causes were recorded. PROMs assessed by WOMAC score and radiographic evaluation to identify signs of implant dysfunction were documented at last follow-up. Results: After a mean follow-up of 4.0 years (0.9-7.7, ±2), only one rerevision (2.3%) was required for persisting instability (polyethylene liner exchange from posterior stabilized to a semi constrained). Short-cemented stems were used for both the femur and tibia in 28 (65%) cases, for the femur alone in 13 (30%) cases, and no stems in two cases. In 31 (72%) cases, a standard posterior stabilised tibial insert was used, while 12 (28%) cases required a semi-constrained insert. The mean WOMAC score was 34.4 (0-80, ±21.7). Mean post-operative arithmetic hip-knee-ankle angle (HKA) was 0.8º varus (from 5º varus to 4º valgus), mean mechanical distal femoral angle was 1.7º valgus (from 2º varus to 5º valgus), and mean mechanical tibia proximal angle was 2.2º varus (from 5º varus to 1º valgus). No radiological evidence of aseptic loosening or periprosthetic radiolucencies were identified. Conclusion: Although current revision TKA implants are not ideal for revision TKA performed with rKA, they are an appealing alternative to MA, especially in cases of early, non-wear-related, unsuccessful MA TKAs. rKA TKA revision using short-cemented stems in conjunction with meticulous preoperative planning is safe in the mid-term.